Reliability-based multidisciplinary design and optimization for twin-web disk using adaptive Kriging surrogate model. (September 2016) - Zhang, Mengchuang; Gou, Wenxuan; Yao, Qin
Compared with the conventional single web disk, the twin-web disk has been designed as the future trend of the high-pressure turbine disk by the US Integrated High Performance Turbine Engine Technology program due to its breakthrough in weight loss, strength, and heat transfer efficiency. However, as a crucial component, the high-pressure turbine disk of aerocraft needs a high reliability and a steady quality at the same time. The traditional deterministic multidisciplinary design of optimization method sometimes could not be able to satisfy both the two requirements and depends heavily on the selection strategy of safety factor. In this article, reliability-based multidisciplinary design optimization has been performed to find a proper shape of twin-web disk with the minimum weight. The structural strength reliability analysis is performed using Monte Carlo simulation and set as the constraints in order to ensure the stability and safety. Kriging approximation is performed to reduce the computational cost. Then, the optimal points obtained by reliability-based multidisciplinary design optimization and common multidisciplinary design optimization are compared. The results show that the reliability-based multidisciplinary design optimization can obtain a better performance and less weight, which could be a reference in designing the twin-web disk for industry.